Orders is orders… aren’t they? Rule bending and rule breaking in the British Army - Kirke, Charles M. St G. (Cranfield University, 2009)
In common with all professional armies, the British Army is a disciplined force. There is a sharply stratified rank structure and formal rules abound. There is a prima facie case therefore that when formal rules are broken or bent the individuals involved are taking part in acts of ‘resistance’ or ‘misbehaviour’ or ‘dissent’, implying a binary opposition of interests between junior and senior. However, in this article I seek to provide a more nuanced approach to identify a range of rule bending and rule breaking processes embedded in the organizational culture at unit level, through a small number of case studies. To assist in the process Goffman’s model of ‘underlife’ is adopted and extended for the British Army case, but only as a framework to assist in locating the observed events in the rich cultural milieu in which they take place. Viewed in this way, rule bending/breaking activity can be seen as complex and intricate events involving both those who break or bend the formal rules and the agents of authority in a continuing social process, part of the weft and warp of everyday life at regimental duty.
To be published in Ethnography, 2009